Efektivitas thermotherapy dalam mengurangi nyeri akut pada pasien acute coronary syndrome: Studi kasus - Muhammad Dwi Ardianto; Anisa Diantri Harjawan; Asep Badrujamaludin (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Acute Coronary Syndrome (ACS) is a major cause of global mortality, with chest pain as one of the primary symptoms that requires effective management. Non-pharmacological interventions such as thermotherapy have been considered as supportive therapy to reduce pain intensity in ACS patients. Purpose: To explore the effectiveness of thermotherapy in reducing pain intensity among patients with Acute Coronary Syndrome in a clinical nursing context. Methods: A descriptive case report design was employed using a comprehensive nursing care approach, including assessment, diagnosis, intervention, implementation, and evaluation. The subject was a 43-year-old female patient diagnosed with Non-ST Elevation Myocardial Infarction (NSTEMI). Pain intensity was assessed using the Numeric Rating Scale (NRS). Thermotherapy was administered three times within a 12-hour interval, with each session lasting 15–20 minutes. Results: Thermotherapy demonstrated a clinically meaningful reduction in pain intensity, with scores decreasing from 4 (moderate pain) to 1 (mild pain) within 24 hours. Improvements in physiological parameters, particularly blood pressure stabilization, were also observed. Conclusion: The intervention contributed to enhanced patient comfort and relaxation without adverse effects.   Keywords: Acute Coronary Syndrome; Nursing Care; Thermotherapy; Pain.   Pendahuluan: Acute Coronary Syndrome (ACS) merupakan salah satu penyebab utama kematian di dunia, dengan gejala utama berupa nyeri dada yang memerlukan penatalaksanaan efektif. Intervensi non-farmakologis seperti thermotherapy dapat digunakan sebagai terapi pendukung dalam menurunkan intensitas nyeri pada pasien ACS. Tujuan: Untuk mengeksplorasi efektivitas thermotherapy dalam menurunkan intensitas nyeri pada pasien Acute Coronary Syndrome dalam konteks praktik keperawatan klinis. Metode: Penelitian ini menggunakan desain studi kasus deskriptif dengan pendekatan asuhan keperawatan yang meliputi pengkajian, diagnosa, intervensi, implementasi, dan evaluasi. Subjek penelitian adalah pasien Ny. L usia 43 tahun dengan diagnosis Non-ST Elevation Myocardial Infarction (NSTEMI). Pengukuran nyeri menggunakan Numeric Rating Scale (NRS). Intervensi thermotherapy diberikan sebanyak tiga kali dalam interval 12 jam dengan durasi 15–20 menit setiap sesi. Hasil: Pemberian thermotherapy menunjukkan penurunan intensitas nyeri yang bermakna secara klinis dari skala 4 (nyeri sedang) menjadi skala 1 (nyeri ringan) dalam 24 jam. Selain itu, terdapat perbaikan parameter fisiologis terutama stabilisasi tekanan darah. Simpulan: Intervensi ini juga meningkatkan kenyamanan pasien tanpa efek samping yang dilaporkan.   Kata Kunci: Acute Coronary Syndrome; Asuhan Keperawatan; Nyeri; Thermotherapy,